Breakfast at Tiffany’s. From page to screen. The making of a classic. Transformation of gender relations (Colloquia Comparativa Litterarum, 2025)
The aim of this article is to explore how the film adaptation of Truman Capote’s novella Breakfast at Tiffany’s translated the literary original into cinematic language. My claim is that the essential transfigurations ensued in terms of gender relations. The question of what motivated them, and how they impacted the cult status which the movie work acquired, is approached by focusing on the transformations from the perspective of the dramatic structure. Through the use of script development tools: type of narration, thematic premise, central question, controlling idea, mediation, protagonists, setting, and the ways in which casting, style of cinematography and music interact with them, I will attempt to pinpoint and analyse the key differences.
Keywords: screen adaptation; dramatic structure; gender roles; integration into society